KEKERABATAN PLASMA NUTFAH JAMBU METE BERDASARKAN MARKA RANDOM AMPLIFIED POLYMORPHIC DNA - Randriani, Enny; Listyati, Dewi; ., Syafaruddin (Jurnal Tanaman Industri dan Penyegar, 2011)
Genetic Relationship of Cashew Germplasm Based on Random Amplified Polymorphic DNA. Cashew production in Indonesia stilllow (300-463 kg/ha/year) caused by genetic materials used for the cultivation were not superior variety, therefore, some effort to find superiorvariety with high production must be improved. To support those efforts needs wide variation of plant genetic resources. Nowd ays, characteristic dataof cashew germplasm in BALITTRI based on morphological characters, so needed molecular approach to get genetic characteristic s, geneticrelationship and specific characters such as high production marker, one of some techniques that we can use is RAPD marker. Additionally, RAPDmarker is simple, efficient and accurate. The purpose of this study was to know the genetic variation and relationship among cashew germplasm basedon band pattern of DNA by using RAPD technique. The experiment was conducted at Molecular Biology Laboratory of BB-Biogen, Bogor since Maytill November 2009. Genetic material used were MR 851, PK 36, GG1, Laode Kase, Laode Kapala, JT 27, Arsyad Labone, Wonogiri Merah, A x S,F x M, SM 9, C x M, F x A and BO2 by using 25 primers. The activity consisting germplasm collecting of cashew (14 accessions), followed laboratoryactivities such as: DNA extraction and purification, loading and running of PCR product, RAPD and data analysis. Results shows that 25 primersused are 16 primers shown DNA band pattern, one of them was monomorphism and one specific primer which shown DNA band pattern of cashew,i.e: BO2, SM9 and JT27. Germplasm collection of cashew has wide variation. At 70% coefficient, 14 accessions of cashew were divided to threegroups where first group were content 11 individual (MR 851, PK 36, Laode Kase, GG1, Laode Kapala, A x S, F x A, C x M, Arsyad Labone,Wonogiri Merah, and F x M), while second group were content two individuals (BO2 and SM9). Moreover, in first group itself sh own wide variationamong 11 accessions.